FLIM studies of 22- and 25-NBD-cholesterol in living HEK293 cells: plasma membrane change induced by cholesterol depletion - Ostašov, Pavel; Sýkora, Jan; Brejchová, Jana; Olżyńska, Agnieszka; Hof, Martin; Svoboda, Petr (Chemistry and physics of lipids, 2013)
HEK293 cells stably expressing δ-opioid receptor were labeled first with fluorescent analog of cholesterol, 22-NBD-cholesterol, exposed to cholesterol-depleting agent β-cyclodextrin (β-CDX) and analyzed by fluorescence lifetime imaging microscopy (FLIM). In accordance with chemical analysis of cholesterol level, the total cellular signal of this probe was decreased to half. Distribution of lifetime (τtot) values of 22-NBD-cholesterol, however, when screened over the whole cell area indicated no significant difference between control (τtot=4.9±0.1 ns) and β-CDX-treated (τtot=4.8±0.1 ns) cells. On the contrary, comparison of control (τtot=5.1±0.1 ns) and β-CDX-treated (τtot=4.4±0.1 ns) cells by analysis of 25-NBD-cholesterol fluorescence implied highly significant decrease of lifetime values of this probe. The observation that 22-NBD-cholesterol appears to be indifferent to the changes in the membrane packing in living cells is in agreement with previous studies in model membranes. However, our data indicate that the alternation of plasma membrane structure induced by decrease of cholesterol level by β-CDX makes the membrane environment of NBD moiety of 25-NBD-cholesterol probe a significantly more hydrated. This finding not only encourages using 25-NBD-cholesterol in living cells, but also demonstrates that previously drawn discouraging conclusions on the use of 25-NBD-cholesterol in model membranes are not valid for living cells.
Keywords: HEK293 Cells; buněčná membrána; fluorescenční barviva; Microscopy, Confocal; konfokální mikroskopie; HEK293 buňky; fluorescenční mikroskopie; Cell Membrane; Humans; beta-Cyclodextrins; 4-chlor-7-nitrobenzofurazan; 4-Chloro-7-nitrobenzofurazan; Cholesterol; Fluorescent Dyes; Microscopy, Fluorescence; lidé; beta-cyklodextriny; cholesterol